Brain Distribution and Sexually Dimorphic Expression of Amylin in Different Reproductive Stages of the Zebra Finch (Taeniopygia guttata) Suggest Roles of the Neuropeptide in Song Learning and Social Behaviour - Zachar, Gergely; Montagnese, Catherine; Fazekas, Emese A.; Kemecsei, Róbert G.; Papp, Szilvia M.; Dóra, Fanni; Renner, Éva; Csillag, András; Pogány, Ákos; Dobolyi, Arpád (Frontiers in Neuroscience, 2020)
The expression of the recently identified neuropeptide, amylin, is restricted in rodents since amylin appears only in the postpartum preoptic area and may play a role in the control of parental behaviours and food intake regulation. These processes are substantially different between bird and rodent parents as birds do not lactate but often show biparental care of the offspring. To establish the presence and role of amylin in the bird brain, in the present study, we investigated the distribution of amylin in brains of adult male and female zebra finches in 3 different reproductive stages (i.e. paired without young, incubating eggs or provisioning nestlings) and in unpaired control birds living in same sex flocks. Amylin mRNA was identified in the hypothalamus of zebra finch by RT-PCR, which was also used to produce probes for in situ hybridization. Subsequently, in situ hybridization histochemistry was performed in brain sections, and the labelling signal was quantified and compared between the groups. Amylin showed a much wider brain distribution than that of rodents. A strong and, in some regions, sexually dimorphic label was found in the striatum and several brain regions of the social behavioural network in both males and females. Many regions responsible for the learning of birdsong also contained amylin-positive neurons, and some regions showed sex differences reflecting that vocalisation is sexually dimorph in the zebra finch: only males sing. Area X, a striatal song centre present only in males, was labelled in paired but not unpaired males Area X. Another song centre, the lateral part of the magnocellular nucleus of the anterior nidopallium also contained amylin and had higher amylin label in paired than in unpaired birds. The wider distribution of amylin in birds as compared to rodents, suggests a more general role of amylin in avian species than in mammals. Alternatively, parental care in birds is a more complex behavioural trait, requiring a wider set of brain regions to be involved. The sex differences in song centres, and the changes with reproductive status suggest a participation of amylin in social behaviours and related changes in the singing of males.